Afrotourism in Brazilian World Heritage sites: challenges and opportunities emphasising a decolonial narrative - Ana Maria Vieira Fernandes; Gabrielle Cifelli (Via@)
The Brazilian World Heritage recognised by UNESCO and located in urban centres, like the Historic Centers of Salvador (Bahia) and São Luís (Maranhão), and the archaeological remains of Cais do Valongo ( Rio de Janeiro), reveal themselves as fields of symbolic struggles for the recognition of cultural references of Afro-descendants. This cultural diversity is demonstrated both in its tangible heritage and through the intangible cultural references that express the marks of Afro-Brazilian culture and expose the legacies of slavery in Brazil. Considering the existing narrative reduction in the heritagisation discourses, which frequently highlight the hegemonic colonial heritage, this research seeks to clarify how these Brazilian Heritages are being revealed through Afrotourism from a decolonial narrative, and to what extent local community plays a central role in the challenging process of revelation of the Afro-Brazilian memory and its intangible cultural assets.